Perancangan Pop-Up Book sebagai Media Pengenalan Pengendalian Diri untuk Anak Usia 5-6 Tahun - Hariyanto, Agnes Tea Kirana; Nirwana, Aditya; Sukmaraga, Ayyub Anshari (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
Indonesia, known for its friendly nature, is experiencing symptoms of moral degradation, even among elementary school children. This is also due to various factors such as exposure to harmful content and lack of early character education. The concept of self-control, as the foundation for other character education, should be taught to children so they can differentiate what should and shouldn't be done. The purpose of this design is to introduce self-control to children through an informal learning medium: a pop-up storybook titled